Polypeptide synthesis directed by bacteriophage phi W-14 and by mutants defective in DNA synthesis. - Miller, P B (1984)
The latent period of bacteriophage phi W-14 is approximately 65 min when the doubling time of its host, Pseudomonas acidovorans, is 85 min. Host protein synthesis is shut off relatively slowly, stopping approximately 25 min after infection. There are several phases of phage-specific polypeptide synthesis during the latent period: early polypeptides appear within 10 min after infection; middle polypeptides start to appear between 10 nd 30 min; late polypeptides appear after 30 min. The lengths of time for which individual polypeptides are synthesized vary widely. Several late polypeptides do not appear in the virion. DNA replication is not required for late gene expression. The hypermodified pyrimidine, alpha-putrescinylthymine, appears not to be required in both strands of the DNA duplex for transcription.